Synthesis and Neuroprotective Properties of N -Substituted C -Dialkoxyphosphorylated Nitrones - Piotrowska, Dorota G.; Mediavilla, Laura; Cuarental, Leticia; G¿owacka, Iwona E.; Contelles, Jose¿ Marco; Hadjipavlou-Litina, Dimitra; Lopez-Muñoz, Francisco; Oset-Gasque, María Jesús (American Chemical Society, 2025)
Herein, we report the synthesis and neuroprotective power of some N-substituted C-(dialkoxy)phosphorylated nitrones 4a¿g, by studying their ability to increase the cell viability, as well as their capacity to reduce necrosis and apoptosis. We have identified (Z)-N-tert-butyl-1- (diethoxyphosphoryl)methanimine oxide (4e) as the most potent, nontoxic, and neuroprotective agent, with a high activity against neuronal necrotic cell death, a result that correlates very well with its great capacity for the inhibition of the superoxide production (72%), as well as with the inhibition of lipid peroxidation (62%), and the 5-lipoxygenase activity (45%) at 100 ¿M concentrations. Thus, nitrone 4e could be a convenient promising compound for further investigation.